Mesenchymal Stromal Cell–Derived Small Extracellular Vesicles Induce Ischemic Neuroprotection by Modulating Leukocytes and Specifically Neutrophils. Issue 6 (June 2020) - Wang, Chen; Börger, Verena; Sardari, Maryam; Murke, Florian; Skuljec, Jelena; Pul, Refik; Hagemann, Nina; Dzyubenko, Egor; Dittrich, Robin; Gregorius, Jonas; Hasenberg, Mike; Kleinschnitz, Christoph; et al.
Abstract : Background and Purpose—: Small extracellular vesicles (sEVs) obtained from mesenchymal stromal cells (MSCs) were shown to induce neurological recovery after focal cerebral ischemia in rodents and to reverse postischemic lymphopenia in peripheral blood. Since peripheral blood cells, especially polymorphonuclear neutrophils (PMNs), contribute to ischemic brain injury, we analyzed brain leukocyte responses to sEVs and investigated the role of PMNs in sEV-induced neuroprotection. Methods—: Male C57Bl6/j mice were exposed to transient intraluminal middle cerebral artery occlusion. After reperfusion, vehicle or sEVs prepared from conditioned media of MSCs raised from bone marrow samples of 3 randomly selected healthy human donors were intravenously administered. sEVs obtained from normoxic and hypoxic MSCs were applied. PMNs were depleted in vehicle and MSC-sEV–treated mice. Neurological deficits, ischemic injury, blood-brain barrier integrity, peripheral blood leukocyte responses, and brain leukocyte infiltration were evaluated over 72 hours. Results—: sEV preparations of all 3 donors collected from normoxic MSCs significantly reduced neurological deficits. Preparations of 2 of these donors significantly decreased infarct volume and neuronal injury. sEV-induced neuroprotection was consistently associated with a decreased brain infiltration of leukocytes, namely of PMNs, monocytes/macrophages, and lymphocytes. sEVs obtained from hypoxic MSCs (1% O2 ) had similar effects on neurological deficits and ischemic injury as MSC-sEVs obtained under regular conditions (21% O2 ) but also reduced serum IgG extravasation—a marker of blood-brain barrier permeability. PMN depletion mimicked the effects of MSC-sEVs on neurological recovery, ischemic injury, and brain PMN, monocyte, and lymphocyte counts. Combined MSC-sEV administration and PMN depletion did not have any effects superior to PMN depletion in any of the readouts examined. Conclusions—: Leukocytes and specifically PMNs contribute to MSC-sEV–induced ischemic neuroprotection. Individual MSC-sEV preparations may differ in their neuroprotective activities. Potency assays are urgently needed to identify their therapeutic efficacy before clinical application. Abstract : Supplemental Digital Content is available in the text.